Chronology of Lower and Middle Pleistocene sites in Northern Africa - (:unkn) unknown (My University, 2022)
North Africa, and in particular the Maghreb, is a key region for African prehistory in that it contains sites whose chronology covers the entire Pleistocene period from 2.5 Ma to the Holocene. In terms of culture, it fits into the general pattern of the Stone Age, but it has particularities that make it a region apart with its own cultures. Due to its climate and geographical position, between the desert regions of the south and the Mediterranean Sea to the north, it has offered mankind a diversity of landscapes and environments that are quite unique and favorable to the development of human evolution. Finally, this region gives access to Europe through several maritime passages (Gibraltar, Sicily), which were probably used during the Pleistocene, thus reinforcing the interest in studying this northern part of Africa. The recent development of numerous dating methods has made it possible to reinforce and consolidate the chronostratigraphic framework, which for many years had been based solely on radiocarbon dating. These methods have sometimes even contributed to the confirmation of ‘new’ ideas that have dusted off the existing framework of prehistory. This article presents a chronology of the main ancient sites of the Maghreb dated by different methods whose ages compared to the results obtained by other disciplines participate and contribute to a better understanding of the environmental and cultural framework of prehistoric Man.
Keywords: African Research